Application of ECRS Comprehensive Anomaly Analysis In Zhangjiakou-bohai Fault Belt. Issue 1 (February 2021) - Hong, Li
Abstract: ECRS (earthquake corresponding relevancy spectrum) is one of the statistical methods for quantitative identification of earthquake comprehensive precursor anomalies. It is used to identify and extract precursor anomalies information of observed data. Taking Zhangjiakou-bohai fault belt as the study area, we carry out earthquake comprehensive anomaly analysis on base of ECRS method. According to seismic characteristic of study area, magnitude of target earthquake and initial earthquake in calculation are Ms5 and Ms2, respectively. By case analysis and extrapolation of multi-parameter earthquake relevancy spectrum of different inspection period, we select the proper time-interval which has better prediction efficiency and give quantitative evaluation of research area. The anomaly correspondence rate and earthquake correspondence rate are 6/8 and 8/9, respectively, when anomaly threshold is 0.45 times standard deviation.